2017
DOI: 10.1159/000484167
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to CDK4/6 Inhibitors in Breast Cancer and Potential Biomarkers of Response

Abstract: Randomized clinical trials demonstrated that CDK4/6 inhibitors are highly effective in patients with hormone receptor-positive (HR+), HER2-negative (HER2-) metastatic breast cancer in combination with endocrine therapy. The use of CDK4/6 inhibitors in clinics is becoming common for patients with HR+/HER2- metastatic breast cancer and will certainly increase in the near future. However, patients might show de novo or acquired resistance to these drugs. Molecular alterations have been suggested as determinants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…Its downregulation is described in various tumors, most frequently through promoter methylation, and results in deregulation of cycle and proliferation (16,17). Interestingly, CCNE1 overexpression and loss of CDK inhibitor p21 have been reported as mechanisms of resistance to palbociclib in breast cancer (18).…”
Section: Discussionmentioning
confidence: 99%
“…Its downregulation is described in various tumors, most frequently through promoter methylation, and results in deregulation of cycle and proliferation (16,17). Interestingly, CCNE1 overexpression and loss of CDK inhibitor p21 have been reported as mechanisms of resistance to palbociclib in breast cancer (18).…”
Section: Discussionmentioning
confidence: 99%
“…As the primary target of CDK4/6 inhibitors, RB was considered to be one of the most important biomarkers of sensitivity to therapy. [24][25][26] In this scenario, loss of RB is the evident cause of resistance to CDK4/6 inhibitors, 24 and various preclinical studies have supported this hypothesis. 20,27,28 In addition, some preclinical and clinical studies have also reported that mutations in RB are responsible for the resistance.…”
Section: Cell Cycle-specific Mechanismsmentioning
confidence: 96%
“…The tumor suppressor RB is the aforementioned key checkpoint in the cell cycle. As the primary target of CDK4/6 inhibitors, RB was considered to be one of the most important biomarkers of sensitivity to therapy . In this scenario, loss of RB is the evident cause of resistance to CDK4/6 inhibitors, and various preclinical studies have supported this hypothesis .…”
Section: Mechanisms Of Resistance To Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…Deregulation of the Rb pathway and the expression of cyclin E1 (CCNE1) have been described as mediators of response to CDK4/6 inhibitors (21,28,29). Therefore, we analyzed the mRNA expression of RB1 and CCNE1, as well as a gene expression signature of Rb loss-of- (18,25,27).…”
Section: Response By Baseline Clinical Pathologic and Molecular Chamentioning
confidence: 99%